2020
DOI: 10.1515/htmp-2020-0063
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure evolution of roll core during the preparation of composite roll by electroslag remelting cladding technology

Abstract: In the present study, the comprehensive analyses based on the numerical simulation, in situ observation, and metallographic detection were carried out for the roll core of GCr15/45 carbon steel composite roll manufactured by the new electroslag remelting cladding (ESRC) method. During the ESRC process, the temperature distributions at the different radial and longitudinal positions of the roll core have great changes due to the different degrees of heat conduction from the slag bath, as a result, various micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Based on the previous report by authors, 23) the coarse grains and harmful ferritic Widmanstatten structure were observed in the heat-affected zone of the as-cast GCr15/45 carbon steel composite samples. In order to eliminate the above undesirable microstructure, an isothermal spheroidization annealing treatment was carried out.…”
Section: Isothermal Spheroidization Annealing At the Bimetallic Interfacementioning
confidence: 60%
See 1 more Smart Citation
“…Based on the previous report by authors, 23) the coarse grains and harmful ferritic Widmanstatten structure were observed in the heat-affected zone of the as-cast GCr15/45 carbon steel composite samples. In order to eliminate the above undesirable microstructure, an isothermal spheroidization annealing treatment was carried out.…”
Section: Isothermal Spheroidization Annealing At the Bimetallic Interfacementioning
confidence: 60%
“…21) For the GCr15/45 carbon steel composite billet, few Widmanstatten structures were always generated in the heat-affected zone of the roll core. 23) The Widmanstatten structure is always considered as an overheating defect, its existence generally results in a serious separation of the matrix and reduces the material's toughness and plasticity. Since to the large angle grain boundary has a certain blocking effect on the crack growth, and the fact of the larger grain size, the less grain boundary, so few obstacles are encountered during the crack growth, and finally, a higher brittleness performance is obtained.…”
Section: Tensile Testing Of the Interface Specimensmentioning
confidence: 99%